Simulación de monte carlo para estimar la viabilidad de proyectos bajo la metodología scrum : aplicación - Salcedo Salazar, Juan Diego (2018)
The aim of this research work is to estimate the projects viability carried out_x000D_ by the Scrum Methodology, to do that a evaluation model has been designed as the_x000D_ research work main proposal._x000D_ A prototype of software made in Python has been developed in order to automate_x000D_ the proposed proposal. The prototype has as input a project and it Scrum_x000D_ processes. The uncertainly in the processes duration and client tolerance are contemplated_x000D_ in the present model._x000D_ The viability of a project is intended to be used by projects leaders in project_x000D_ planning stage development, in this way preventive actions can be taken prior to the_x000D_ project execution stage._x000D_ In order to test the effectiveness of the Monte Carlo Simulation and the evaluation_x000D_ model, tests have been carried out on 4 real projects provided by the software_x000D_ development consulting and consulting company, CONASTEC